Seeking the right to food : food activism in South Africa - Nkrumah, Bright, 1982- (Cambridge University Press, 2021)
Despite a constitutional right to food, a comprehensive social security structure, being a net exporter of agricultural products and maintaining a rising GDP, freedom from hunger remains a pipedream for millions of South Africans. With a constant surge in food prices, the availability of sustenance is often seriously threatened for all of South Africa's population. While the underprivileged majority residing in townships often demonstrate their discontent for poor service delivery on the streets, they rarely channel this strategy into taming food inflation. This study seeks to understand this irony and examine ways in which this trend could be reversed. Proposing a compelling argument for food activism, Bright Nkrumah suggests ways of mobilising disempowered groups to reclaim this inherent right. Presented alongside historical and contemporary case studies to illustrate the dynamics of collective action and food security in South Africa, he draws from legal, social and political theory to make the case for 'activism' as a force for alleviating food insecurity.
Title from publisher's bibliographic system (viewed on 06 Aug 2021).
Keywords: Food security -- South Africa.; Human rights movements -- South Africa.; Food supply -- Government policy -- South Africa.; Food supply -- Social aspects -- South Africa.; Right to food -- South Africa.; South Africa -- Social policy.